UTILIZANDO A INFORMÁTICA COMO ALICERCE PARA O ENSINO DA MATEMÁTICA - Sakis, Maria A. S.; Fahl, Daniel; Pereira, Tânia M.; Costa, Juliane S. P.; Corrente, Antônio E. (Salão do Conhecimento, 2013)
Resumo